Composition, Artistic Harmony and Logical Solution in Karl Pavlovich Bryullov's "The Last Day of Pompey" - Bobur Jovlievich , Qorjovov (International Journal of Psychosocial Rehabilitation, 2020)
This article provides an artistic, scientific analysis of Karl Pavlovich Bryullov's The Last Day of Pompeii and discusses how perfectly the realities of life are interpreted in the play using symbolic means of expression and imagery. In particular, the expressive features and artistic, logical, and ideological aspects of the fragmented car wheel in the center of the work were studied, and the art (science) of artistic analysis as well as opinions, conclusions, and conclusions based on ancient human views, assumptions, and beliefs were expressed.